Una nueva especie de Sisyrinchium (Iridaceae: Sisyrinchieae) del estado de Durango, México - Espejo-Serna, Adolfo; Lopez-Ferrari, Ana Rosa; Ceja-Romero, Jacqueline (Instituto de Ecología, A.C., 1999)
Sisyrinchium cholewae Espejo, López-Ferrari & Ceja is described from plants collected in the state of Durango, México. S. cholewae can be distinguished from all other known Mexican species of Sisyrinchium in its subaquatic habitat, its white flowers with basally (ca. 1-2 mm) connate perianth and in its spathulate, ascendent and apically rounded tepals, bearing a brilliant yellow spot at their base